2014
DOI: 10.3402/gha.v7.25323
|View full text |Cite
|
Sign up to set email alerts
|

Using diaries to explore the work experiences of primary health care nursing managers in two South African provinces

Abstract: BackgroundSouth Africa is on the brink of another wave of major health system reforms that underscore the centrality of primary health care (PHC). Nursing managers will play a critical role in these reforms.ObjectiveThe aim of the study was to explore the work experiences of PHC clinic nursing managers through the use of reflective diaries, a method hitherto under-utilised in health systems research in low- and middle-income countries.DesignDuring 2012, a sub-set of 22 PHC nursing managers was selected randoml… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
40
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 25 publications
1
40
0
3
Order By: Relevance
“…Nursing managers’ self-ratings on the domain of staff management contradicts the findings from the diary and job satisfaction studies where they expressed difficulties in managing unplanned staff absences and human resources shortages (15, 36). Therefore, these PHC managers need training in staff management to steer complex health system changes in facing staff shortages (46).…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…Nursing managers’ self-ratings on the domain of staff management contradicts the findings from the diary and job satisfaction studies where they expressed difficulties in managing unplanned staff absences and human resources shortages (15, 36). Therefore, these PHC managers need training in staff management to steer complex health system changes in facing staff shortages (46).…”
Section: Discussionmentioning
confidence: 75%
“…The leadership and management functions that nursing managers encounter daily involve decision-making, delegating work, problem-solving, communication, and acting with moral integrity (1, 15, 36). That only one-third of nursing managers indicated the need for leadership and management training in this study contradicts the findings of the job satisfaction survey among the same managers which found that the majority wanted training in leadership and management (15).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations